1991
DOI: 10.2527/1991.69104097x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium soaps of fatty acids on postpartum reproductive function in beef cows

Abstract: Twelve multiparous Simmental cows (584 kg) were used to determine the influence of calcium soaps of fatty acids (CSFA) incorporated in a range supplement on postpartum reproductive characteristics. Cows were assigned randomly to receive a control [C; containing grain sorghum (GS) and soybean meal (SBM)] or CSFA-based (containing Megalac [a source of CSFA], GS, and SBM) supplement. Supplements plus prairie hay were individually fed. Diets were isonitrogenous and met the NEm requirement for heavy-milking beef co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
5

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 0 publications
3
36
1
5
Order By: Relevance
“…Duration of the supplementation period is another potential reason for the discrepancy between the results of the present study and others (Hightshoe et al, 1991;Hawkins et al, 1995). In the present study, a supplementation period of 14 d was used based on previous studies from our laboratory (Lopes et al, 2009(Lopes et al, , 2011.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Duration of the supplementation period is another potential reason for the discrepancy between the results of the present study and others (Hightshoe et al, 1991;Hawkins et al, 1995). In the present study, a supplementation period of 14 d was used based on previous studies from our laboratory (Lopes et al, 2009(Lopes et al, , 2011.…”
Section: Discussionmentioning
confidence: 72%
“…Adding calcium soaps of FA to the diet increased serum concentrations of P 4 in bovine females (Hightshoe et al, 1991;Hawkins et al, 1995). Greater concentrations of P 4 before and after breeding are associated with enhanced fertility (Folman et al, 1973) and embryonic survival (Mann et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in pregnancy rate at 45 d post insemination [5], ovarian follicle growth [6] and steroidogenesis [7] have all been reported. It has been suggested that the mechanism involves enhanced ovarian activity through the following: improved energy status [8], increased availability of cholesterol for steroid synthesis [9] and increased circulating insulin concentrations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Astrup et al (1976) and Palmquist and Conrad (1978) also observed an increase in total lipid concentration following fat supplementation. Supplementation of the ration with fat increased both the triglyceride content (Marty and Block, 1990) and the cholesterol concentration (Sharma et al, 1978;Wrenn et al, 1978;Marty and Block, 1990;Hightshoe et al, 1991) of the blood plasma.…”
Section: Tablementioning
confidence: 99%